Thermodynamic parameters of the chromatographic equilibrium distribution process of amphiphilic compound by HPLC. Part I: Fatty acid - Bravo, Bélgica; Chávez, Gerson; Ysambertt, Fredy; Graciaa, Alain; Lachaise, Jean; Antón, Raquel; Salager, Jean Louis; Márquez, Nelson (Ciencia, 1970)
The retention behaviour of fatty acids on a reverse phase HPLC column is reported. Retention increases as the acetonitrile/methanol mobile phase becomes richer in acetonitrile. For a given solvent mixture, retention increases (linearly) with the acid chain length. Retention factor (k) is dimensionless and independent on any geometrical parameters of the column or HPLC system. It could be considered to be a thermodynamic characteristic of the adsorbent-compound-eluent system. HPLC experiments carried out at different temperatures allow to plot the variation of the ln k vs. 1/T, and to calculate the DG°, DH° and DS° of transfer of one molecule from the mobile phase to the stationary phase. According to a Van”™t Hoff expression, the retention decreases as temperature increases. Both DH° and DS° are negative, a result that corroborates that the adsorption of the n-alkyl chains onto the stationary phase is favourable from the energetic point of view, and that it increases the molecular order.